Education-Productive Sector Alliance, A Bet Worth. Case: Valle del Cauca Agroecological Industry - Vásquez Rizo, Fredy Eduardo; Gabalán Coello, Jesús; Flórez Bolaños, Jaime (Revista Colombiana de Investigaciones Agroindustriales, 2014)
The impact assessment is presented for the, “Alliance for the sugarcane agro-ecologic sector” Project, in the Valle del Cauca department, conducted by the National Ministry of Education, and coordinated by the Universidad Autonoma de Occidente – UAO. Various factors were analyzed, like: Coverage, learning process, teacher training, SABER 11 test results in high schools, impact and learning environments. A mixed investigation took place, that gathered all the quantitative and qualitative elements, with the purpose of maximizing the existing information resources and respond effectively to the information needs of the investigation, analyzing diverse sources (state, educational, business), related in some way tothe Alliance project. Para citar este artículo Vásquez, F., Gabalán, J. y Flórez, J. (2014). Alianza Educación-Sector Productivo, una apuesta que vale la pena. Caso: Sector Agroecológico del Valle del Cauca. Revista colombiana de investigaciones agroindustriales, 1(1), 80-93. DOI: http://dx.doi.org/10.23850/24220582.118